2014
DOI: 10.1073/pnas.1408048111
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells modulate granulomatous inflammation in an HLA-DP2 transgenic murine model of beryllium-induced disease

Abstract: Susceptibility to chronic beryllium disease (CBD) is linked to certain HLA-DP molecules, including HLA-DP2. To elucidate the molecular basis of this association, we exposed mice transgenic (Tg) for HLA-DP2 to beryllium oxide (BeO) via oropharyngeal aspiration. As opposed to WT mice, BeO-exposed HLA-DP2 Tg mice developed mononuclear infiltrates in a peribronchovascular distribution that were composed of CD4 + T cells and included regulatory T (T reg ) cells. Beryllium-responsive, HLA-DP2-restricted CD4 + T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 23 publications
2
63
0
Order By: Relevance
“…Cd (Hemdan, 2008), Cu 2+ , and Hg 2+ (Schedle et al, 1998) decreased IFN-γ. By contrast, in our results, Mn exposure caused a significant increase of IFN-γ (P b 0.05) in the 4 × 10 −4 and 8 × 10 −4 mmol/L Mn groups for 24 h, in all treatment groups for 36 h, and in the 4 × 10 −4 and 6 × 10 − 4 mmol/L Mn groups for 48 h. Some studies also found that TiO 2 NPs (Delgado-Buenrostro et al, 2014) and BeO (Mack et al, 2014) exposure increased IFN-γ. The mechanism of Mn-induced change of IFN-γ mRNA expression is unclear and needs further investigation.…”
Section: Contents Lists Available At Sciencedirectsupporting
(Expert classified)
“…Cd (Hemdan, 2008), Cu 2+ , and Hg 2+ (Schedle et al, 1998) decreased IFN-γ. By contrast, in our results, Mn exposure caused a significant increase of IFN-γ (P b 0.05) in the 4 × 10 −4 and 8 × 10 −4 mmol/L Mn groups for 24 h, in all treatment groups for 36 h, and in the 4 × 10 −4 and 6 × 10 − 4 mmol/L Mn groups for 48 h. Some studies also found that TiO 2 NPs (Delgado-Buenrostro et al, 2014) and BeO (Mack et al, 2014) exposure increased IFN-γ. The mechanism of Mn-induced change of IFN-γ mRNA expression is unclear and needs further investigation.…”
Section: Contents Lists Available At Sciencedirectsupporting
(Expert classified)
“…Since CBD is a known cause of chronic granulomatous lung disease, occupational health screening and immunological testing should be utilized when appropriate [62]. A recent publication of an experimental model of CBD recapitulates many of the features found in human disease, providing a new tool to help understand the pathogenic mechanism of granulomatous lung disease involved in CBD and sarcoidosis [63].…”
Section: Environmental Studies Of Sarcoidosis Etiologymentioning
confidence: 99%
“…While IL-1R signaling has been shown to be important in murine models of nickel-induced hypersensitivity [20], release of biologically-active IL-1α is not dependent upon the inflammasome and could account for these effects [21]. For example, beryllium exposure in the lung induced rapid release of IL-1α and not IL-1β; however, after long-term exposure to beryllium, IL-1β is released [22,23]. Thus, other factors besides beryllium may be involved or required for priming of the pro-IL-1β signal.…”
Section: Recognition Of Metals By the Innate Immune Systemmentioning
confidence: 99%
“…In the case of the lung or other target organs, this may involve the development of granulomatous inflammation as the T cells attempt to wall off the persistent metal and regulate inflammation. In addition to effector cells, regulatory T cells can be induced by metal ions and regulate inflammation [23]. As tissue damage progresses, deposition of collagen and fibrosis impairs organ function, leading to progressive disease and, in some cases, death.…”
Section: Effector T Cells In the Elicitation Phase Of Hypersensitivitymentioning
confidence: 99%